The Role of Insulin Deficiency in Cognitive Dysfunction in Patients with Type 1 Diabetes Mellitus - Yu. V. Bykov (Фундаментальная и клиническая медицина)
Type 1 diabetes mellitus is a chronic autoimmune disease with a onset in childhood and adolescence. Neurological disorders are among the most frequent complications of type 1 diabetes mellitus and might lead to cognitive impairment termed as diabetic encephalopathy. Besides regulating blood glucose, insulin have neuroprotective and pro-cognitive effects through its action on insulin receptors in the brain, promoting the production of neurotransmitters, long-term potentiation, synaptic plasticity, and neuronal differentiation. By enhancing abovementioned processes responsible for learning and memory, insulin improves cognitive functioning. Insulin deficiency triggers cognitive dysfunction and diabetic encephalopathy via mitochondrial dysfunction, oxidative stress, and disorganisation of glucose metabolism which alter functioning of glucose transporter proteins and induce pericyte loss, ultimately compromising integrity of the blood-brain barrier. Intranasal delivery of exogenous insulin, which bypasses the bloodbrain barrier, may serve as an efficient therapeutic strategy for correcting cognitive impairment in patients with diabetic encephalopathy. Further research is needed to uncover and understand the effects of exogenous insulin on cognitive functions in patients with type 1 diabetes mellitus.